APLIKASI DESAIN GRAFIS UNTUK PENGEMBANGAN KONTEN PROMOSI PRODUKSI PENGRAJIN ANYAMAN PURUN DESA BURAI - Anita Desiani; Erwin Erwin; Yuli Andriani; Sri Indra Maiyanti; Adi Muzakir; Ananda Pratiwi; Andika Cristian Lubis; Puspa Sari (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2023)
Burai Village is located in Tanjung Batu District, Ogan Ilir Regency, South Sumatra has woven purun crafts as its characteristic. Burai Village women make handicrafts made from purun in a manual way to fill their free time. The results of woven purun in Burai Village are usually sold directly or by receiving requests from people who visit Burai Village so that the woven purun made from Burai Village is only known by those who are and visit in the area. This marketing limitation is caused by the lack of public knowledge related to marketing strategies and technological knowledge in marketing the products sold. It is necessary to empower purun woven craftsmen through the use of graphic design applications to increase marketing and buying and selling of purun chicken in Burai Village. The stages in this activity are surveys, preparation of activities, delivery of materials and evaluation of activities. After the implementation of this activity, the participants have sufficiently understood how to use the application which can be seen from the increase in the results of the pre-test and post-test knowledge scores that the participants have done. And it is also expected to be implemented on a sustainable scale.